Evaluation of earthquake prediction efficiency of significant change point of mobile gravity near Yishu zone under weak earthquake background - Jiajun Zheng; Litao Yang; Shupeng Li; Wei Xiong; Min Dong; Yuzhen Liu; Hanpeng Lu; Fengji Wang; Jing Wu; Hailin Liu; Guomin Chi (地震科学进展, 2025)
The area around which a gravitational field changes significantly is usually accompanied by measurement points with significant changes. To carry out analysis of the gravity field variation around the Yishu zone based on the analysis of regional variation, the temporal variation of the measuring points around the significant change area was analyzed in detail to verify its correspondence with surrounding earthquakes. In this study, the data difference between July 2022 and the previous period and August 2015 near the Yishu zone was calculated, and peripheral measuring points with significant regional changes were selected through mapping to analyze the preliminary correspondence between their time series changes and the surrounding earthquakes. The long-term data were analyzed and verified using an earthquake prediction efficiency evaluation software. The results showed that: ① The Guangrao area is affected by ground subsidence, the Changyi area is affected by changes in groundwater level, and the Zaozhuang and Zhangzhuang areas have some correspondence with the surrounding earthquakes. ② Only one out of ten evaluation items in the threshold category and trend-turning category of the five significant change measurement points failed to meet the evaluation criteria. It can be preliminarily concluded that the significant change measurement points near the Yishu zone have a good monitoring efficiency for ML3.0 earthquakes within 100 km of the measurement points.